2018
DOI: 10.17513/use.36766
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological and Hydrochemical Condition of Small Rivers in the Arctic Zone of Yakutia

Abstract: Для оценки изменения химического состава водных объектов с учетом возможного воздействия производственных процессов были проведены натурные обследования малых рек в арктической зоне Якутии. В полевой сезон 2017 г. были взяты пробы воды и проведены натурные измерения гидрологических характеристик-руч. Красный и р. Лев.Ыт-Юрях. Работы по анализу режима малых рек рассматриваемой территории ранее не проводились. Рассматриваемые водные объекты расположены в среднем течении р. Индигирка. Они относятся к категории ма… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The entire area sits on the permafrost [59]. Permafrost makes ecosystems in the region fragile and less resistant to external effects of global change [60]. The ecosystems in Sakha Republic are represented by native endemic plant and animal species, many of which are endangered and protected.…”
Section: Indigenous Communities In the Republic Of Sakhamentioning
confidence: 99%
See 1 more Smart Citation
“…The entire area sits on the permafrost [59]. Permafrost makes ecosystems in the region fragile and less resistant to external effects of global change [60]. The ecosystems in Sakha Republic are represented by native endemic plant and animal species, many of which are endangered and protected.…”
Section: Indigenous Communities In the Republic Of Sakhamentioning
confidence: 99%
“…Yakovleva reported that the construction of the ESPO pipeline and the railway in Aldan uluus in the south of the Republic of Sakha had a negative effect on hunting, reindeer herding, as well as the migration of animals and fish [20]. Furthermore, specific natural characteristics of the region (e.g., permafrost, seismic activity, formation of glaciers, and floods) may cause the damage of pipelines along the route and consequently result in oil spill [60]. Oil leakages at the ESPO station in Ölüökhüme uluus in west Sakha Republic occurred in 2006 and 2010 as a result of human error during repairs [84].…”
Section: Economic Developmentmentioning
confidence: 99%